Fear or failure: Why victims of domestic violence retract from the criminal justice process - Artz, Lillian (SA crime quarterly, 2016)
In 2008/9 MOSAIC,with the assistance of the Gender, Health & Justice Research Unit (UCT), embarked on research that sought to identify the factors that contribute to domestic violence victims withdrawing from the legal process before they finalise protection orders (POs) applied for under the Domestic Violence Act (DVA). This study was based on the 2008 work of this author who, in partnership with MOSAIC, interviewed 365 domestic violence victims in the Western Cape about their engagement with and retraction from the criminal justice process.The second tier of this project – reported on here – emerged with more focused interview schedules and the addition of eight jurisdictions from which the sample was drawn. The findings from this study were extensive and pointed to a range of personal, systemic and structural reasons why Domestic Violence Act [DVA] applicants disengage from the criminal justice process. This article will limit its focus on three areas that are relevant to the decision by survivors to withdraw their applications for protection orders: the history and severity of violence, deadly threats, and key findings relating specifically to experiences of DVA applicants with the courts.